Inclusive education: ideas vs reality - Jovanović Popadić, Ana M (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2017)
This paper examines inclusive education from a critical point of view. After defining the concept of inclusion, it underlines the significance of inclusive education and its implementation in different circumstances. We mention the law and analyse the attitude of a certain number of teachers (who work in regular primary schools and special school for primary and secondary education in Kruševac) toward inclusive education. After a concise statistical overview, we analyse their experience, competence and working conditions, and we also consider the opinions about the effects of inclusive education compared to education in a special school. The final part is a kind of critical review of the current situation in education. It also offers the possibilities for overcoming the problems identified during the research and stresses the unsustainability of current practice of inclusive education.